2020
DOI: 10.2147/ott.s273172
|View full text |Cite
|
Sign up to set email alerts
|

<p>Acute Myeloid Leukemia with <em>NUP98-RARG</em> Gene Fusion Similar to Acute Promyelocytic Leukemia: Case Report and Literature Review</p>

Abstract: Retinoic acid receptor gamma (RARG) belongs to the nuclear receptor superfamily and has 90% homology to RAR alpha (RARA) and RAR beta. The promyelocytic leukemia (PML)-RARA fusion gene has been implicated in acute promyelocytic leukemia (APL). RARG gene rearrangement has been identified in a rare subtype of acute myeloid leukemia (AML) that resembles APL. To date, only 10 cases of gene rearrangements involving RARG (nucleoporin [NUP]98-RARG, promyelocytic leukemia protein-RARG, cleavage and polyadenylation-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…Two types of NUP98–RARG transcripts were identified. One was an in‐frame fusion, in which exon 12 of NUP98 (NM_016320.5) was fused to exon 4 of RARG (NM_000966.6) (Figure S1A ) , which was the same as previously reported 2,9–14 . The other one was an out‐of‐frame fusion, with exon 12 of NUP98 fused to exon 5 of RARG (Figure S1B ), which led to premature termination of the new fusion gene after 521 amino acids and destroyed the DBD and LBD domains of the RARG gene.…”
Section: Casesupporting
confidence: 62%
See 2 more Smart Citations
“…Two types of NUP98–RARG transcripts were identified. One was an in‐frame fusion, in which exon 12 of NUP98 (NM_016320.5) was fused to exon 4 of RARG (NM_000966.6) (Figure S1A ) , which was the same as previously reported 2,9–14 . The other one was an out‐of‐frame fusion, with exon 12 of NUP98 fused to exon 5 of RARG (Figure S1B ), which led to premature termination of the new fusion gene after 521 amino acids and destroyed the DBD and LBD domains of the RARG gene.…”
Section: Casesupporting
confidence: 62%
“…Till now, about 10 cases of NUP98 – RARG rearrangement have been reported. Review of the NUP98–RARG rearrangement showed they were associated patients who were all morphologically and immunophenotypically resembling APL, 2,9,12–14 except one case of AML‐M5 10 . The initiation of ATO and/or ATRA in case of NUP98 – RARA ‐negative leukaemia is not the satandard practice according to guidelines.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to clinical finding, NUP98-RARG -postive APL was sensitive to ATRA treatment in murine system, which possibly was attributed to the different genetic backgrounds. Up to now, additional NUP98-RARG -positive APL patients have been reported by different groups including our group, and the breakpoint for NUP98-RARG was conserved, which located at NUP98 exon-12 and RARG exon-4 [ 100 104 ]. Though NUP98-RARG transformed murine HSPCs was sensitive to ATRA treatment ex vivo, all of NUP98-RARG -positive APL patients showed resistance to ATRA in clinic, and chemotherapy was required for their CR achievement.…”
Section: Rarg Rearrangement In Variant Aplmentioning
confidence: 99%
“…In fact, another patient with CPSF6-RARG has been reported in 2019 [ 3 ]. Since then, two more cases of CPSF6-RARG and two cases of NUP98-RARG have been reported [ 4 , 5 , 6 , 7 ]. Therefore, the number of reported patients has reached eight cases for CPSF6-RARG and six for NUP98-RARG .…”
mentioning
confidence: 99%